The factors that affect customers’ revisit intention of Hotels: an empirical study applied on Saudi Arabia - Abd al-Hamid, Muhammad Abd al-Qadir; Fawzi, Shayma Farid (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
This study aimed to empirically test the factors that affect customers’ revisit intention of hotels based on the importance of this promising sector to the Saudi economy. the study adopted the S-O-R model to investigate how consumers' emotional reactions (O) were influenced by environmental stimuli (S), and how these emotional reactions affected customers’ behavioral responses (R) by investigating how atmospheric variables and perceived quality trigger hotel customer satisfaction and in return affect their revisit intention. a self-administered questionnaire was distributed on 5-star international hotels located in Riyadh in Saudi Arabia, with 134 valid responses. the structural equation model was used to empirically test the proposed hypotheses with Amos statistical package. the research found that “assurance” as one of the service quality dimensions had a significant impact on the hotel customer satisfaction. in addition, “word-of mouth” and “customer satisfaction” had a direct and positive impact on customers’ revisit intentions to the same hotels. from a practical point of view, the study recommends that hotel managers ensure continuous training to their employees, even for part-timers, to ensure that their employees are knowledgeable and can make better decisions in the future, especially to handle guests’ queries or complaints. هدفت الدراسة إلى اختبار العوامل التي تؤثر على نية العملاء في إعادة زيارة نفس الفنادق، وذلك لأهمية هذا القطاع الواعد للاقتصاد السعودي. اعتمدت الدراسة نموذج S-O-R لاختبار مدى تأثير المحفزات البيئية (S) على ردود الفعل العاطفية للمستهلكين (O)، وعلى الاستجابات السلوكية للعملاء (R)، وذلك بدراسة مدى تأثير متغيرات البيئة المحيطة وجودة الخدمة المدركة في إرضاء عملاء الفندق، والذي في المقابل يؤثر على نيتهم في تكرار الحصول على الخدمة من نفس الفندق. تم توزيع استبيان مدار ذاتيا من قبل نزلاء الفنادق الدولية من فئة 5 نجوم والتي تقع في مدينة الرياض بالمملكة العربية السعودية، وبتجميع عدد ١٣٤ استجابة صالحة للتحليل استخدمت الدراسة (Structural equation modeling (SEM لاختبار فروض الدراسة من خلال برنامج الحزمة الإحصائية AMOS. من نتائج البحث وجد تأثير معنوي لمتغير "الضمان" كأحد أبعاد جودة الخدمة كان له تأثير كبير على رضا عملاء الفنادق، بالإضافة إلى التأثير المعنوي لكل من "الكلام المنقول" و"رضا العملاء" على نوايا العملاء لإعادة زيارة نفس الفنادق. وتوصي الدراسة مديري الفنادق بضمان التدريب المستمر لموظفيهم، حتى بالنسبة للموظفين بدوام جزئي للتأكد من أن موظفيهم يمكنهم اتخاذ قرارات أفضل في المستقبل والتي تخص التعامل مع استفسارات وشكاوى النزلاء.